A computational approach to quantitatively define sarcomere dimensions and arrangement in skeletal muscle. (November 2021) - Cisterna, Barbara; Malatesta, Manuela; Zancanaro, Carlo; Boschi, Federico
Highlights: Definition of parameters characterizing the sarcomere and myofibril arrangement. Semi-automatic routine to measure the parameters on ultrastructural (TEM) images. Routine tested on euploid and trisomic (Down syndrome) skeletal muscle. Ability to quantify muscular disorders as sarcomere shape/arrangement. Abstract: Background and objective: The skeletal muscle is composed of integrated tissues mainly composed of myofibers i.e., long, cylindrical syncytia, whose cytoplasm is mostly occupied by parallel myofibrils. In section, each myofibril is organized in serially end-to-end arranged sarcomeres connected by Z lines. In muscle disorders, these structural and functional units can undergo structural alterations in terms of Z-line and sarcomere lengths, as well as lateral alignment of Z-line among adjacent myofibrils. In this view, objectifying alterations of the myofibril and sarcomere architecture would provide a solid foundation for qualitative observations. In this work, specific quantitative parameters characterizing the sarcomere and myofibril arrangement were defined using a computerized analysis of ultrastructural images. Methods: computerized analysis was carried out on transmission electron microscopy pictures of the murine vastus lateralis muscle. Samples from both euploid (control) and trisomic (showing myofiber alterations) Ts65Dn mice were used. Two routines were written in MATLAB to measure specific structural parameters on sarcomeres and myofibrils. The output included the Z-line, M-line, and sarcomere lengths, the Aspect Ratio (AsR) and Curviness (Cur) sarcomere shape parameters, myofibril axis (α angle), and the H parameter (evaluation of sequence of Z-lines of adjacent myofibrils). Results: Both routines worked well in control (euploid) skeletal muscle yielding consistent quantitative data of sarcomere and myofibril structural organization. In comparison with euploid, trisomic muscle showed statistically significant lower Z-line length, similar M-line length, and statistically significant lower sarcomere length. Both AsR and Cur were statistically significantly lower in trisomic muscle, suggesting the sarcomere is barrel-shaped in the latter. The angle (α) distribution showed that the sarcomere axes are almost parallel in euploid muscle, while a large variability occurs in trisomic tissue. The mean value of H was significantly higher in trisomic versus euploid muscle indicating that Z-lines are not perfectly aligned in trisomic muscle. Conclusions: Our procedure allowed us to accurately extract and quantify sarcomere and myofibril parameters from the high-resolution electron micrographs thereby yielding an effective tool to quantitatively define trisomy-associated muscle alterations. These results pave the way to future objective quantification of skeletal muscle changes in pathological conditions. Short abstract: The skeletal muscle is composed of integrated tissues mainly composed of myofibers i.e., long, cylindrical syncytia, whose cytoplasm is mostly occupied by parallel myofibrils organized in serially end-to-end arranged sarcomeres. Several pieces of evidence have highlighted that in muscle disorders and diseases the sarcomere structure may be altered. Therefore, objectifying alterations of the myofibril and sarcomere architecture would provide a solid foundation for qualitative observations. A computerized analysis was carried out on transmission electron microscopy images of euploid (control) and trisomic (showing myofiber alterations) skeletal muscle. Two routines were written in MATLAB to measure nine sarcomere and myofibril structural parameters. Our computational method confirmed and expanded on previous qualitative ultrastructural findings defining several trisomy-associated skeletal muscle alterations. The proposed procedure is a potentially useful tool to quantitatively define skeletal muscle changes in pathological conditions involving the sarcomere.